UPAYA SAVE THE CHILDREN DALAM MENANGANI PERNIKAHAN ANAK DI NIGERIA - Kinanta, Vio; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This research analyzes Save the Children's efforts to address child marriage in Nigeria. Child marriage remains a critical issue affecting children's development and well-being, and Nigeria is a country with a high rate of child marriage. The high rate of child marriage in Nigeria is influenced by inequalities that are gender norms, socio-cultural factors such as ethnicity and religion, as well as poverty, low education levels, and rural locations. Save the Children, as an organization engaged in the protection and provision of children's rights worldwide, is involved in efforts to reduce child marriage in Nigeria. This research uses qualitative methods, with data collection techniques through literature studies. This research uses a pluralist perspective and the theory of International Non-Governmental Organizations. The results of this study are that Save the Children is working to address child marriage in Nigeria by acting as an implementer, agent of change and partnership, this includes conducting research, implementing policy and legislative advocacy, implementing women's empowerment and community education and collaborating with international organizations, communities, governments and community groups. Keywords: Child Marriages, Save the Children, INGO, Child Rights